Death Art - Loghmani, Mohammad (Loghmani, 2006)
Verzio FF Submission The film presents the intertwinement of art and death. Starting with the adorning of the dead body, the film explores the art of painting, sculpting, blacksmithing, dancing and performing inspired by death.